2018
DOI: 10.3928/01913913-20170703-13
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Congenital Cataract in Eyes With Microcornea

Abstract: Early surgical intervention for congenital cataract in eyes with microcornea can result in favorable outcomes with an acceptable rate of postoperative complications. [J Pediatr Ophthalmol Strabismus. 2018;55(1):30-36.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Details on visual acuity and surgical complications have been meticulously reported in previous studies of cataract removal in eyes with MC; hence, corneal properties were the focus of this study. 8,32,33 In conclusion, our study revealed that the patients with MC and normal axial length possess specific parameters, including significantly smaller corneal diameter and thicker CCT than the patients in the control groups. There were no significant differences in ECD and average keratometry.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Details on visual acuity and surgical complications have been meticulously reported in previous studies of cataract removal in eyes with MC; hence, corneal properties were the focus of this study. 8,32,33 In conclusion, our study revealed that the patients with MC and normal axial length possess specific parameters, including significantly smaller corneal diameter and thicker CCT than the patients in the control groups. There were no significant differences in ECD and average keratometry.…”
Section: Discussionmentioning
confidence: 52%
“…Details on visual acuity and surgical complications have been meticulously reported in previous studies of cataract removal in eyes with MC; hence, corneal properties were the focus of this study. 8,32,33…”
Section: Discussionmentioning
confidence: 99%
“…Increased IOP as an early sign of glaucoma often arise especially in one year postoperatively. 9 Although IOP rise was not found in this case, nevertheless routine followup is required and important to monitor IOP.…”
Section: Discussionmentioning
confidence: 70%
“…However, the use of posterior chamber IOL was considered as a safe technique. 9 In this case, on follow up examinations showed good IOP results and the patient was planned to have a periodically visit schedule. Patients were also given glasses to maximize visual acuity on the RE.…”
Section: Discussionmentioning
confidence: 85%
“…38 Matalaia et al found a rate of 10.6% of secondary glaucoma in those with microcornea, with incidence not significantly different between early and late age at surgery. 39 The IATS found smaller corneal diameter to be an independent risk factor for all glaucoma-related adverse events, 6,34 as did Swamy et al in 2007. 8…”
mentioning
confidence: 81%